ANALISIS PERILAKU SOSIAL REMAJA KORBAN BULLYING PADA SISWA SMP NEGERI 2 TONDANO MINAHASA SULAWESI UTARA - Tiwa, Tellma M. (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to describe the Behavior of Adolescent Bullying Victims in junior high school children or early teens. The subjects in this study were the primary subject as the initial subject and the secondary subject as a supporter of the truth of the data. Another objective of this research is to find out: (i) how to socialize victims of bullying. (ii) the behavior of the victims of bullying. (iii) the impact of bullying victims' behavior. (iv) factors causing the behavior of victims of bullying. The approach in this research is a qualitative approach in the form of case study research. Collecting data using interviews, observation and documentation. The data analysis technique uses the Miles and Huberman (2014) model. The results of the study show that (i) the ways of socializing the two victims of bullying are different, victims of PK socialize by balancing their surroundings, while victims of the Constitutional Court are more likely to close themselves off. (ii) The behavior of bullying victims is in the form of physical bullying, such as being hit and verbal bullying, such as being ridiculed with bad names. (iii) the impact of bullying victims' behavior on PK with their social environment operating as usual. While in the Constitutional Court the impact is not good. (iv) the factors causing the victims of PK and MK are family factors.